A History of China - Roberts, J. A. G., 1935- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'It has been said that the twenty-first century will be China's century. Such a remark highlights the importance of being informed about China's long and tumultuous history. J.A.G. Roberts traces the main course of that history, from the earliest times, through the centuries of imperial government, to the present day. Chapters on China's imperial history identify the main political and economic changes, whilst introducting key social themes. Turning to the modern period, Roberts then traces the dramatic evenuts of the Opium Wars, the 1911 Revolution and the Republican era. The book ends with a detailed discussion of China under Communist rule and a wide-ranging review of new developments, including China's economic achievements and its costs. Thoroughly revised and expanded in the light of the latest research, and now featuring a helpful chronology, this up-to-date, authoritative overview of China's past is ideal for students and general readers alike'--Provided by publisher.
Machine generated contents note: -- List of Maps -- Preface -- Acknowledgements -- Introduction -- Maps -- The Prehistory and Early History of China -- From the Period of Division to the Tang Dynasty -- The Song and Yuan Dynasties -- The Early Modern Period: The Ming and the Early Qing -- China in the Late Qing -- Republican China, 1911-49 -- Revolutionary China, 1949-76 -- From the Era of Deng Xiaoping to the Present Day -- Notes -- Chronology -- Further Reading -- Index.
Includes bibliographical references and index.
Keywords: China -- History